An Overview of Patient Responses During Hemodialysis in Chronic Kidney Disease - Eliya Warzaniyah; Mustiah Yulistiani (UM Purwokerto Press, 2026)
Background: Chronic kidney disease (CKD) is a progressive and irreversible impairment of kidney fungction, leading to the body’s inability to maintain fluid, electrolyte, and metabolic balance. Hemodialysis serves as an effective renal replacement therapy for patient with CKD; however, it may also cause adverse side effects. Method: The study employed a case study design with a descriptive approach. A total sampling technique was used, involving 12 respondents. Data collection was conducted through observation sheets and interview guides. Results: The responses observed in chronic kidney disease patients undergoing hemodialysis at RSUD Ajibarang included hypertension (91.7%), dizziness (33.3%), muscle cramps (25%), nausea (8.3%), fever (8.3%), chills (8.3%), and chest pain (8.3%). Conclusion: The most common responses experienced by hemodialysis patient at RSUD Ajibarang were hypertension, dizziness, and muscle cramps.